2014
DOI: 10.1021/jm5008177
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Biological Evaluation of (3R)-1,2,3,4-Tetrahydro-7-hydroxy-N-[(1S)-1-[[(3R,4R)-4-(3-hydroxyphenyl)-3,4-dimethyl-1-piperidinyl]methyl]-2-methylpropyl]-3-isoquinolinecarboxamide (JDTic) Analogues: In Vitro Pharmacology and ADME Profile

Abstract: JDTic analogues 4–15 which have the hydroxyl groups replaced with other groups were synthesized and their in vitro efficacy at the μ, δ, and κ opioid receptors determined and compared to JDTic using [35S]GTPγS assays. Compounds 4, 5, 6, 13, 14, and 15 had Ke = 0.024, 0.01, 0.039, 0.02, 0.11, and 0.041 nM compared to the Ke = 0.02 nM for JDTic at the κ receptor and were highly selective for the κ receptor relative to the μ and δ opioid receptors. Unexpectedly, replacement of the 3-hydroxyl substituent of the 4-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 45 publications
(115 reference statements)
0
23
0
Order By: Relevance
“…Coupling of 6-hydroxynapthalene-2-carboxylic acid with 60a in the presence of N -ethoxycarbonyl-2-ethoxy-1,2-dihydroquinoline (EEDQ) in dimethylformamide as solvent, heated at 100 °C for 3 h, furnished analogue 37 . Boc-7-carbamoyl- d -Tic-OH, prepared in three steps as previously reported, 21 was coupled with diamine 60a to yield 73b , which yielded 41 after the removal of the Boc-protecting group. Similarly, Boc-7-fluoro- d -Tic-OH, also previously reported, 21 was employed for the synthesis of 73d which upon Boc-deprotection, furnished compound 45 .…”
Section: Resultsmentioning
confidence: 99%
“…Coupling of 6-hydroxynapthalene-2-carboxylic acid with 60a in the presence of N -ethoxycarbonyl-2-ethoxy-1,2-dihydroquinoline (EEDQ) in dimethylformamide as solvent, heated at 100 °C for 3 h, furnished analogue 37 . Boc-7-carbamoyl- d -Tic-OH, prepared in three steps as previously reported, 21 was coupled with diamine 60a to yield 73b , which yielded 41 after the removal of the Boc-protecting group. Similarly, Boc-7-fluoro- d -Tic-OH, also previously reported, 21 was employed for the synthesis of 73d which upon Boc-deprotection, furnished compound 45 .…”
Section: Resultsmentioning
confidence: 99%
“…[3] In another recent study we reported that the replacement of the hydroxy group in the 4-(3-hydroxyphenyl) moiety of JDTic with a hydrogen or fluoro group gave compounds 3a and 3b both of which were potent and selective kappa opioid receptor antagonists. [4] (Fig. 1) As a continuation of our structural activity relationship (SAR) studies directed toward the kappa opioid receptor as well as the development of potential pharmacotherapies for CNS disorders, compounds 4a–f were synthesized and evaluated in vitro using a [ 35 S]GTPγS binding assay at the μ, δ, and κ opioid receptors and their ADME properties were established.…”
Section: Introductionmentioning
confidence: 99%
“…Coupling of amine 21 and commercially available Boc-( R )-1,2,3,4-tetrahy-droisoquinoline-3-carboxylic acid using conditions similar to those used for the synthesis and deprotection of 3 afforded 10 . To prepare the target compound 11 , amine 21 was coupled with Boc-7-fluoro-( R )-1,2,3,4-tetrahydroisoquinoline-3-carboxylic acid, prepared as previously reported, 21 using DCC and HOBt, followed by deprotection with hydrogen chloride in methanol.…”
Section: Resultsmentioning
confidence: 99%